Digital Muamalah Transaction Transformation: Fintech Integration with TSR Principles - Erviana, Nita; Nugroho, Lucky (Baca Dulu Publisher, 2025)
This study examines the transformation of digital muamalah contracts in Islamic fintech, focusing on the integration of the Tawhid String Relationship (TSR) and Transaction Cost Theory (TCT) principles. The emerging phenomenon is a shift from conventional transactions to digital platforms that comply with Islamic principles. However, there is a gap between technological developments and Islamic jurisprudence (fiqh) understanding regarding Islamic digital transactions, leading to challenges in Islamic compliance. This study uses a qualitative approach with secondary data collection through relevant literature. The results show that the application of technologies such as blockchain and smart contracts can increase efficiency and transparency in digital transactions, but still require strict supervision to ensure compliance with Islamic principles. Maqasid Sharia serves as a foundation to ensure that every innovation continues to support the welfare of the community. The theoretical implication of this study is the development of TSR and TCT theories in the context of Islamic fintech, while the practical implication is the need for clearer regulations and more intensive education to increase Muslim literacy regarding digital contracts. This study also provides suggestions for the development of more efficient and Islamic fintech platforms in Indonesia that comply with Islamic principles.